One third of the world's growth and inequality - Danny T. Quah (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2002)
This paper studies growth and inequality in China and India—two economies that account for a third of the world's population. By modelling growth and inequality as components in a joint stochastic process, the paper calibrates the impact each has on different welfare indicators and on the personal income distribution across the joint population of the two countries. For personal income inequalities in a China-India universe, the forces assuming first-order importance are macroeconomic: growing average incomes dominate all else. The relation between aggregate economic growth and within-country inequality is insignificant for inequality dynamics. – China ; distribution dynamics ; Gini coefficient ; headcount index ; India ; poverty ; world individual income distribution
Keywords: D30; O10; O57; 330; Wirtschaftswachstum; Einkommensverteilung; China; Indien